2002
DOI: 10.1074/jbc.m112073200
|View full text |Cite
|
Sign up to set email alerts
|

A Forkhead/Winged Helix-related Transcription Factor Mediates Insulin-increased Plasminogen Activator Inhibitor-1 Gene Transcription

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is an important regulator of fibrinolysis by its inhibition of both tissue-type and urokinase plasminogen activators. PAI-1 levels are elevated in type II diabetes and this elevation correlates with macro-and microvascular complications of diabetes. Insulin increases PAI-1 production in several experimental systems, but the mechanism of insulin-activated PAI-1 transcription remains to be determined. Deletion analysis of the PAI-1 promoter revealed that the insulin resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
0
21
2
Order By: Relevance
“…Additively-The high levels of circulating PAI-1 found in diabetics could result from insulin stimulation of PAI-1 production as suggested previously (2,14). High levels of oxidative stress associated with diabetes might also contribute to maintenance of high PAI-1 (29).…”
Section: Insulin and Oxidative Stress Activate The Pai-1 Promotermentioning
confidence: 83%
See 2 more Smart Citations
“…Additively-The high levels of circulating PAI-1 found in diabetics could result from insulin stimulation of PAI-1 production as suggested previously (2,14). High levels of oxidative stress associated with diabetes might also contribute to maintenance of high PAI-1 (29).…”
Section: Insulin and Oxidative Stress Activate The Pai-1 Promotermentioning
confidence: 83%
“…We previously demonstrated that insulin activated the PAI-1 promoter through a forkhead-related response element (TTATTT) at Ϫ52/Ϫ43 of the PAI-1 promoter (14). Insulinincreased PAI-1 gene expression was inhibited by the expression of the DNA binding domain of forkhead.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 gene transcription is positively regulated by various transcription factors, including Sp1 (12,36), Forkhead (61), and the hypoxia-inducible factor (27). Interestingly, an Sp1 and PAI-1 regulator, transforming growth factor ␤ (16, 18), is overexpressed at the mRNA level in Net mutant cells (Table 1), raising the possibility that it may contribute to the increase of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…18 -21 Interestingly, FOXO1 was previously shown to bind to the insulin response element (IRE) of the PAI-1 promoter, although it had little effect on insulin-driven PAI-1 expression. 22,23 This suggests that another Fox protein(s) plays a role in insulin-mediated induction of the PAI-1 gene.FOXC2 is shown to be upregulated by insulin signaling in adipocytes and functions as a key regulator in adipose tissues in counteracting insulin resistance in adult mice as well as human subjects of insulin resistance or obesity. 24,25 FOXC2 upregulates the transcription of the RI subunit of protein kinase A (PKA) to augment the ␤-adrenergic-cAMP-PKA response, leading to increased sensitivity to insulin.…”
mentioning
confidence: 99%